Continuous ventricular cerebrospinal fluid drainage with intracranial pressure monitoring for management of posttraumatic diffuse brain swelling - Andrade,Almir Ferreira de (2011)
BACKGROUND: Ventricular drainage has played an important role in the management of traumatic brain-injured patients. The aim of the present study was describe outcomes in a series of 57 patients with diffuse brain swelling underwent to intracranial pressure (ICP) monitoring. METHOD: Fifty-eight patients with diffuse posttraumatic brain swelling, were evaluated prospectively. The Glasgow Coma Scale (GCS) scores of patients varied from 4 to 12. Patients groups divided according to GCS and age. Patient neurological assessment was classified as favorable, unfavorable, and death. RESULTS: Mechanisms of injury were vehicle accidents in 72.4% and falls in 15.6%. 54% of patients had GCS scores between 6 and 8. There were no statistical differences, regarding outcome, between groups separated by age. In the adults group (n=47), 44.7% evolved favorably. CONCLUSION: Our results indicate a poor prognosis in patients with brain swelling. We believe that continuous ventricular CSF drainage with ICP monitoring is a simple method as an adjunct in the management of these patients.